2016
DOI: 10.1080/17518253.2016.1185166
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium, kinetic and thermodynamic biosorption studies of Hg(II) on red algal biomass ofPorphyridium cruentum

Abstract: Among a variety of microbial materials employed for biosorption, algae have added advantages of non-toxic and autotrophic nature. In this study, biosorption of Hg(II) was studied with red algal biomass of Porphyridium cruentum. The parameters affecting biosorption such as dosage of biosorbent, pH, contact time, initial metal concentration, temperature and effect of foreign metal cations in binary system were evaluated. Kinetic data were described with the help of pseudofirst-order and pseudo-second-order kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…At higher pH (pH < 6), a reduction in biosorption was also observed. This is because, at high pH values, there is a probability for precipitation of metal ions as salts or hydroxides in solution (Zaib et al 2016). Similar results were observed using other strains of B. subtils, where the pH pzc of the biosorbent was 1.5 (Ng 2018).…”
supporting
confidence: 81%
“…At higher pH (pH < 6), a reduction in biosorption was also observed. This is because, at high pH values, there is a probability for precipitation of metal ions as salts or hydroxides in solution (Zaib et al 2016). Similar results were observed using other strains of B. subtils, where the pH pzc of the biosorbent was 1.5 (Ng 2018).…”
supporting
confidence: 81%
“…The randomness of the adsorption process was confirmed by the positive values of ∆S • . This finding agrees with Zaib et al [114], who used the red algal biomass of Porphyridium cruentum. The equilibrium biosorption data was analyzed using biosorption isothermal models, which revealed a correlation between the mass of the solute adsorbed per unit mass of the equilibrium sorbent.…”
Section: Discussionsupporting
confidence: 92%
“…Huang and Lin [8] studied Hg adsorption by Sargassum in an aqueous solution which found pH 8-10 was the optimum adsorption capability with 70% removal of heavy metals. Another study was reported for red algae which could adsorb 99% Hg at pH 7-10 [34]. Similar to this study, the adsorption efficiency of Hg by S. crassifolium had almost reached 98% removal from industrial wastewater at pH 9.…”
Section: Resultssupporting
confidence: 87%